Is there a Green Dividend of National Redistribution? - Eren Gürer; Alfons J. Weichenrieder (The Journal of Economic Inequality, 2023)
Abstract~~CO2 emissions are disproportionately caused by more affluent consumers. In the political debate, this fact has triggered the demand for income redistribution and wealth taxes not only to reduce inequality but also to reduce CO2 emissions. This paper calculates the possible size of a green dividend, i.e., a reduction in total national CO2 emissions, of redistribution in 26 countries and concludes that, for most EU countries, it is negative if the redistribution is efficient, in the sense that it keeps average incomes constant. If the redistribution introduces inefficiencies that lead to total income losses, the negative green dividend, otherwise associated with additional redistribution, may be avoided.
Keywords: Q56; D12; D30; 300; Environment; Redistribution; CO2 emissions; Inequality; Green dividend